2023
DOI: 10.3390/ijerph20043621
|View full text |Cite
|
Sign up to set email alerts
|

Social Environment and Attitudes toward COVID-19 Anti-Contagious Measures: An Explorative Study from Italy

Abstract: Social and cultural aspects (i.e., political decision making, discourses in the public sphere, and people’s mindsets) played a crucial role in the ways people responded to the COVID-19 pandemic. Framed with the Semiotic-Cultural Psychological Theory (SCPT), the present work aims to explore how individual ways of making sense of their social environment affected individuals’ perception of government measures aimed at managing the pandemic and the adherence to such measures. An online survey was administered fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 92 publications
0
3
0
Order By: Relevance
“…First and foremost, the emphasis on family and communal ties in addressing the challenges of isolation may have played a crucial role. This emphasis likely heightened the sense of collectivism among citizens during the lockdown ( Travaglino and Moon, 2021 ; Gennaro et al, 2023 ). This shift reflects a noteworthy departure from the conventional characterization of Italy as an individualistic society.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First and foremost, the emphasis on family and communal ties in addressing the challenges of isolation may have played a crucial role. This emphasis likely heightened the sense of collectivism among citizens during the lockdown ( Travaglino and Moon, 2021 ; Gennaro et al, 2023 ). This shift reflects a noteworthy departure from the conventional characterization of Italy as an individualistic society.…”
Section: Discussionmentioning
confidence: 99%
“…Several social factors, including gender ( Galasso et al, 2020 ), trust ( Gennaro et al, 2023 ), and political affiliation ( Gollwitzer et al, 2020 ), have been shown to influence attitudes, behaviors, and health outcomes related to the pandemic. Among these factors, cultural orientation in the form of individualism–collectivism has received significant attention in academic research ( Ashraf et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Since the outbreak of the pandemic, numerous studies have investigated the worldwide negative impact of COVID-19 on mental health [1][2][3][4][5][6][7][8][9]. Both the pandemic and the strict measures implemented for its containment (i.e., social distancing, self-isolation, stringent hygiene procedures, and lockdown) have disrupted people's lives and well-being in nearly every nation [9][10][11][12][13][14][15]. Among the detrimental consequences are the documented increase in symptoms such as stress, anxiety, depression, psychosomatic problems, and insomnia which, on the one hand, have been found to pose serious risk factors for mental health [16][17][18][19][20][21], and on the other hand, have aggravated the already high socio-economic burden of the pandemic (e.g., rising unemployment rate and loss of productivity) [19,22].…”
Section: Introductionmentioning
confidence: 99%
“…Coping with the crisis posed significant challenges for national healthcare systems. The sum of these factors generated negative effects and physiological and mental health issues among both the general population [2][3][4][5][6][7][8][9][10] and healthcare workers (HCWs) [11][12][13][14][15]. Front-line medical staff came under both physical and psychological pressure.…”
Section: Introduction 1psychological Impact Of Covid-19 Pandemic On H...mentioning
confidence: 99%